Habitat decline of the largest known Indo-Pacific humpback dolphin (Sousa chinensis) population in poorly protected areas associated with the hypoxic zone - Guo, Lang; Luo, Dingyu; Yu, Ri-Qing; Zeng, Chen; Huang, Nuoyan; Wang, Hongri; Wu, Yuping (Frontiers in Marine Science, 2022)
Reserve planning based on the distribution investigation of the core habitat of wild cetaceans is a powerful conservation strategy to protect target species. However, studies of core habitats and their variations in large-scale distributed cetaceans are limited. In this study, we conducted seven years (2015-2021) boat-based field observation surveys with highly applicable and generalized methods to analyze the habitat changes and how the changes influence the world’s largest known Indo-Pacific humpback dolphin (Sousa chinensis) population in the Pearl River Estuary (PRE), China. Our findings revealed that there are 3204 km2 of dolphin habitat in the PRE, and dolphin distribution preferences were related to nutrients and biological resources. The decreasing trend of dolphin sighting rates in most areas (73.2%) indicated that the dolphin habitat has declined, and the annual habitat decline rate (2.83%, 95% CI: 0.58% 5.08%) was basically consistent with the population decline rate. The annual habitat decline rate in the hypoxic zone revealed from the low dolphin sighting rates from March to October in the hypoxic zone was 0.43% faster than that in the non-hypoxic zone, indicating the long-term sustained effects of summer hypoxia on the dolphin population. The existing reserve has prevented partial habitat decline to some extent. However, more than 82.3% of the habitat has not been effectively protected and encountered the threat of pollution and hypoxic stress. This study offers new scientific evidence in developing effective monitoring strategies for humpback dolphin populations in the PRE, and also could help establish spatial planning and management measures of reserve habitats.